Pengembangan Bahan Ajar Menulis Berita Straight News dan Feature dengan Pendekatan Jurnalisme Profetik - Herdiana, Aan; Abineri, Reza (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This study aims to (1) develop a module for writing straight news and feature articles using a prophetic journalism approach, and (2) assess the feasibility of the module. The research method used is research and development (R&D) with the 4D model (Define, Design, Develop, and Disseminate) by Thiagarajan. The instruments used in this study include validation sheets for experts in content, language, and media. Data were collected through observation, interviews, documentation, and questionnaires. The results of this development research indicate that the developed product meets the validation criteria, with expert validation reaching 87.9%, broken down as follows: content expert 89%, language expert 84.7%, media expert 90.25%, and student response questionnaires reaching 83%. Based on these results, it can be concluded that the developed module for writing straight news and feature articles with a prophetic journalism approach is valid and suitable for use in learning